Evaluating the Implementation of Hospital Information System Using the HOT-Fit Framework: A Case Study at RSUD Prof. Dr. H. Aloei Saboe, Indonesia - Kasmianti Kasmianti; Dwi Iskandar (International Journal of Public Health, 2025)
The adoption of Hospital Information Systems (HIS) is a crucial step toward improving healthcare service delivery, especially in public hospitals in developing countries. RSUD Prof. Dr. H. Aloei Saboe, a referral hospital in Gorontalo, Indonesia, has implemented the SIMRS Khanza system to digitize inpatient registration and medical documentation. However, limited evaluation has been conducted to assess its effectiveness beyond technical performance. This study aims to evaluate the implementation of SIMRS Khanza using the Human-Organization-Technology Fit (HOT-Fit) framework, which examines the alignment between users, institutional support, and system quality. A qualitative descriptive method was employed, involving in-depth interviews, non-participatory observations, and document reviews with eight informants, including medical record officers, system coordinators, and hospital management. The findings reveal that although most users reported improved efficiency and satisfaction, several issues persist: incomplete training, limited adherence to SOPs, and system performance lags during peak hours. Organizational support was present but inconsistent, and documentation policies lacked specificity for digital contexts. Technologically, the system demonstrated stable output, but responsiveness and integration require enhancement. The synthesis of findings suggests that success in HIS implementation is contingent upon not only system reliability but also continuous user engagement, structured training, and dynamic policy support. Therefore, a holistic strategy integrating human, organizational, and technological components is essential to optimize SIMRS performance and sustainability.